2007
DOI: 10.1002/mrd.20729
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cytotrophoblast cell–cell fusion is associated with reduced Syncytin and increased apoptosis in patients with placental dysfunction

Abstract: Preeclampsia (PE), Hemolysis Elevated Liver Enzymes and Low Platelets (HELLP)-syndrome, and intrauterine growth restriction (IUGR) are associated with abnormal placentation. In early pregnancy, placental cytotrophoblasts fuse and form multinuclear syncytiotrophoblasts. The envelope gene of the human endogenous retrovirus-W, Syncytin, is a key factor for mediating cell-cell fusion of cytotrophoblasts. This study investigated clinical parameters of PE and HELLP-associated IUGR and analyzed the cell-cell fusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
126
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 56 publications
8
126
1
1
Order By: Relevance
“…Disturbed trophoblast fusion and syncytiotrophoblast formation has been linked to the pathogenesis of pregnancy-related complications such as pre-eclampsia, intrauterine growth restriction (IUGR), and haemolysis elevated liver enzymes and low platelets (HELLP)-syndrome (Gauster et al, 2009;Langbein et al, 2008) A number of proteins have been identified as crucial regulators of trophoblast cell fusion. Syncytin-1, a protein encoded by a human endogenous retrovirus-W envelope protein gene (Mi et al, 2000), is abundantly expressed in placental trophoblasts and appears to be critical for trophoblast fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbed trophoblast fusion and syncytiotrophoblast formation has been linked to the pathogenesis of pregnancy-related complications such as pre-eclampsia, intrauterine growth restriction (IUGR), and haemolysis elevated liver enzymes and low platelets (HELLP)-syndrome (Gauster et al, 2009;Langbein et al, 2008) A number of proteins have been identified as crucial regulators of trophoblast cell fusion. Syncytin-1, a protein encoded by a human endogenous retrovirus-W envelope protein gene (Mi et al, 2000), is abundantly expressed in placental trophoblasts and appears to be critical for trophoblast fusion.…”
Section: Introductionmentioning
confidence: 99%
“…In PE, growing evidence implicates abnormalities in syncytiotrophoblast (SynT) in the villous exchange region of the placenta. [1][2][3][4][5][6] SynTs are thin, fetal-derived cells that lie between the maternal blood flowing through the villous exchange region of the placenta and the fetal blood flowing through fetal vessels in the highly vascularized villi. This surface is essential for fetomaternal communication and exchange and is formed through the differentiation of SynT from the underlying villous cytotrophoblast cells under the control of the transcription factor GCM1 (glial cells missing 1).…”
mentioning
confidence: 99%
“…It is also know to suppress apoptosis in choriocarcinoma cells (41) and low levels of syncytin-1 have been linked to placental dysfunction in pre-eclampsia (42)(43)(44). Most significantly expression of syncytin-1 has also been shown to suppress staurosporin-induced apoptosis in Chinese hamster ovary (CHO) cells (45) Although there is significant evidence for syncytin-1 conferring a growth/survival advantage in malignant cells, there is also evidence that its expression induces demyelination and cell death in oligodendrocytes which is consistent with the protein playing a causative role in neurodegenerative disease (48).…”
Section: Discussionmentioning
confidence: 99%